ICEduTech 2016Report from a Scientific Conference in RMIT, Melbourne - Smyrnova-Trybulska, Eugenia (International Journal of Research in E-learning, 2016)
ICEduTech (http://icedutech-conf.org/) is a scientific conference addressing the real topics as seen by teachers, students, parents, and school leaders. Scientists, professionals, and institutional leaders are invited to be informed by experts, and to increase the understanding of what education needs and how to achieve it.